Green Practices in the Hotel Industry: The Push and Pull Factors - Norhani Aripin; Noor Afza Amran; Natrah Saad; Noor Rohin Awaluddin (International Journal of Supply Chain Management, 2018)
The objective of this study is to determine the motivational factors and barriers that influence the implementation of green practices in Malaysian hotels. The environmental issue in Malaysia has a long history, which began with river pollution because of tin mining operations. It has now become more critical as air pollution and waste disposal by the hotel industry have a negative impact on the environment. A total of 86 questionnaires were received from four-star and five-star hotels in Selangor, Kuala Lumpur and Putrajaya. The dependent variable is green practices, while the independent variables are motivational factors and barriers. Data from the questionnaires were analyzed using the Partial Least Squares-Structural Equation Modeling approach and the SmartPLS software. Motivational factors are found to have a significantly positive relationship with the implementation of green practices. However, the barriers to green practices do not have statistical significance. The study contributes to existing literature by introducing factors that encourage the Environmental Management System (EMS) and also recommends the study of more strong factors in green practices research.